Pengaruh Pola Asuh Orang Tua Terhadap Aspek Perkembangan Sosial Emosional Siswa Kelas III Sekolah Dasar - Rumbarak, Martha; Airlanda, Gamaliel Septian (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine whether there is an influence of parenting style on aspects of the social-emotional development of children which will produce mentality that is able to compete at the elementary school level. This research is a quantitative study using pre-experimental either one or various aspects of social emotional development groups of third grade elementary school students who are observed to determine whether there is influence from the influence of parenting styles. The subjects of this study were the parents of 20 students of grade III Soromasen State Elementary School, 12 parents of YPK Yobi Elementary School, and 18 parents of YPK Sambrawai Elementary School. The data collection technique was in the form of distributing questionnaires to parents of third grade elementary school students. The data analysis technique for testing the hypothesis was carried out to find out whether there was or was not the influence of Parenting Patterns (X) on aspects of the social emotional development of third grade elementary school students (Y) partially. The data used is the t-test hypothesis used to determine the significance of the effect of the independent variables partially or individually on the dependent variable. Based on the results of the t test, it is known that sig 0.001 <0.05 or -1.092 > 0.2845, so there is a negative influence on parenting patterns on aspects of social emotional development of third grade elementary school students. The results of this study show the negative influence of parenting patterns on the emotional social development aspects of third grade elementary school students.